2018
DOI: 10.1016/j.virol.2018.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a novel mycovirus in Alternaria alternata manifesting two-sided effects: Down-regulation of host growth and up-regulation of host plant pathogenicity

Abstract: A double-stranded RNA (dsRNA) mycovirus was detected in a strain of Alternaria alternata showing impaired growth phenotypes. The A. alternata strain is the Japanese pear pathotype, which produces a host-specific AK-toxin. Sequence analysis of the viral genome dsRNAs revealed that this mycovirus consists of five dsRNAs and is evolutionarily related to members of the family Chrysoviridae; the virus was named Alternaria alternata chrysovirus 1 (AaCV1). AaCV1-ORF2 protein accumulated in dsRNA-high-titer sub-isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 47 publications
1
74
0
Order By: Relevance
“…Briefly, the identified dsRNA viruses are three chrysoviruses, one totivirus, one endornavirus, one tetramycovirus and one virus that groups with a still undefined clade of viruses. With the exception of the chrysovirus identified in Alternaria alternata , which was already reported as Alternaria alternata chrysovirus 1 (Okada et al ., ), the other eight viruses have low identity with protein already reported in databases and hence are to be considered as new viral species. In specific, for dsRNA viruses, we observed identity percentages ranging from 77% for the putative coat protein of the totivirus and 64% of the RNA‐dependent RNA polymerase (RdRP) domain of the same virus, down to 28% of the endornavirus polyprotein.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, the identified dsRNA viruses are three chrysoviruses, one totivirus, one endornavirus, one tetramycovirus and one virus that groups with a still undefined clade of viruses. With the exception of the chrysovirus identified in Alternaria alternata , which was already reported as Alternaria alternata chrysovirus 1 (Okada et al ., ), the other eight viruses have low identity with protein already reported in databases and hence are to be considered as new viral species. In specific, for dsRNA viruses, we observed identity percentages ranging from 77% for the putative coat protein of the totivirus and 64% of the RNA‐dependent RNA polymerase (RdRP) domain of the same virus, down to 28% of the endornavirus polyprotein.…”
Section: Resultsmentioning
confidence: 99%
“…In a more recent report, Okada et al . () reported mycovirus‐mediated effects on Alternaria alternata disease development in Japanese pear. Also in such case, thanks to the presence of a mycovirus, the fungus displayed the overproduction of an effector which enhanced its virulence in the host plant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Okada et al . (Okada et al ., ) recently reported mycovirus‐mediated effects on Alternaria alternata disease development in Japanese pear. The authors demonstrated a Chrysovirus‐mediated enhancement of A. alternata pathogenicity through the overproduction of an effector (AK‐toxin), which is a host‐specific toxin able to induce necrotic spots in leaves.…”
Section: Resultsmentioning
confidence: 99%
“…AaCV1 was isolated from Alternaria alternate Japanese pear pathotype, which infects the susceptible pear cultivar ‘Nijisseiki’, produces AK-toxin and causes Alternaria black spot on the leaves. On the one hand, high titer of AaCV1 severely impaired the growth of A. alternata; on the other hand, it increased AK-toxin production and enhanced virulence of this fungus [35].…”
Section: Discussionmentioning
confidence: 99%